ChemInform Abstract: Copper‐Catalyzed Trifluoromethylation of Arylsulfinate Salts Using an Electrophilic Trifluoromethylation Reagent. Issue 31 (11th July 2013) - Lin, Xiaoxi; Wang, Guimei; Li, Huaifeng; Huang, Yuanyuan; He, Weiming; Ye, Dandan; Huang, Kuo‐Wei; Yuan, Yaofeng; Weng, Zhiqiang
Abstract The presented reaction is compatible with a wide range of functional groups in arylsulfinates (I) expanding the scope of Cu‐catalyzed electrophilic triflouromethylation reactions.